Effectiveness of a psychoeducational intervention for caregivers of People With Dementia with regard to burden, anxiety and depression: A systematic review. (13th January 2020) - Frias, Cindy E.; Garcia‐Pascual, Marta; Montoro, Mercedes; Ribas, Nuria; Risco, Ester; Zabalegui, Adelaida
Abstract: Aim: To assess the effectiveness of psychoeducational interventions with respect to burden, anxiety and depression in family caregivers of People With Dementia living at home. Background: In dementia, the family assumes the role of main caregiver, maintaining the patient in a good state of health. Nevertheless, burden, anxiety and depression may have negative repercussions in caregivers. Therefore, professional supports through psychoeducational programmes are recommended as interventions for improving caregivers' health. Design: A quantitative systematic review. Data Sources: Electronic searches were performed in CINAHL/AMED/CENTRAL/Web of Science/LILACS/PUBMED from January 2005–August 2018. Review Methods: The review was conducted using the JADAD scale to assess bias risk and the quality of the randomized controlled trials (RCTs) and the CONSORT instrument to assess study quality report. The extracted data were reviewed by independent reviewer pairs. The review was reported using PRISMA. Results: A total of 18 RCTs met inclusion criteria. Seven were classified as Technology‐based Interventions and 11 as Group‐based Interventions. Conclusion: Psychoeducational interventions for caregivers allow them to increase their knowledge of the illness, develop problem‐solving skills and facilitate social support. Technology‐based Interventions significantly affect burden while Group‐based Interventions affect anxiety, depression, insomnia and burden and quality of life and self‐efficacy. Impact: Research findings can be used to classify caregivers in future interventions according to illness stage to obtain more precise results. Abstract : 目的: 针对心理教育干预措施对居家痴呆症患者的家庭照护人员在心理负担、焦虑和抑郁情绪方面的有效性进行评价。 背景: 在痴呆症患者家中, 家庭人员充当主要照护人员, 使患者保持良好的健康状态。然而, 心理负担、焦虑和抑郁情绪可能对照护人员产生负面影响。因此, 建议通过心理教育方案来提供专业帮助, 以作为改善照护人员健康状态的干预措施。 设计: 定量系统评估。 数据来源: 通过CINAHL/AMED/CENTRAL/Web of Science/LILACS/PUBMED进行电子搜索(2005年1月至2018年8月)。 评估方法: 本项评估采用JADAD量表, 对偏倚风险和随机对照试验(RCTs)的质量进行评价, 并且使用CONSORT量表来对研究质量报告进行评价。所获取的数据均由独立评估人员对进行评估。本项评估采用PRISMA予以开展。 结果: 共有18项随机对照试验符合纳入标准。其中7项被归类为基于技术的干预措施, 11项被归类为基于群体的干预措施。 结论: 对照护人员进行心理教育干预有助于提高其对疾病的认识, 培养解决问题的能力, 并且促进社会支持力度。基于技术的干预措施对心理负担有显著影响, 而基于群体的干预措施可对焦虑、抑郁情绪、失眠和心理负担以及生活质量和自我效能感产生影响。 影响: 研究发现可用于根据不同疾病阶段对未来干预措施下的照护人员进行分类, 以获得更为精确的结果。